Teacher’s Perceptions and Institutional Preparedness For Implementing AI in Learning Assessment at The Elementary School Level - Saddam Fathurrachman; Novi Eka Saputri (IQRO: Journal of Islamic Education, 2025)
The digital transformation in education encourages the integration of Artificial Intelligence as a supportive tool in various instructional processes, including student assessment. This study aims to explore the perceptions of primary school teachers and the readiness of schools in implementing AI for learning assessment. A descriptive qualitative approach was employed, supported by descriptive quantitative data analysis. Data were collected from 15 elementary school teachers at Bogor Regency through questionnaires and semi-structured interviews, focusing on three key aspects: teachers’ knowledge of AI, their attitudes toward its use, and the readiness of school infrastructure. The findings indicate that the majority of teachers (73%) expressed positive attitudes toward AI implementation, with 60% demonstrating basic knowledge of AI concepts. However, only 40% reported that their schools were adequately equipped with the necessary infrastructure to support such technological integration. Further qualitative analysis reveals that while positive attitudes are a promising starting point, they must be supported by intensive training programs and clear policy frameworks to ensure the contextual and sustainable use of AI in assessment practices.